Effect of six weeks 1000 mg/day vitamin C supplementation and healthy training in elderly women on genes expression associated with the immune response - a randomized controlled trial - Małgorzata Żychowska; Agata Grzybkowska; Mariusz Zasada; Anna Piotrowska; Danuta Dworakowska; Olga Czerwińska-Ledwig; Wanda Pilch; Jędrzej Antosiewicz (Taylor & Francis Group, 2021)
Background In this study, we investigated the effects of supplementation and exercise on the expression of genes associated with inflammation like CCL2, CRP, IL1, IL6, IL10 mRNA in elderly women. Methods Twenty four participants divided randomly into two groups were subjected to 6 weeks of the same health training program (three times per week). SUP group (supplemented, n = 12, mean age 72.8 ± 5.26 years and mean body mass 68.1 ± 8.3 kg) received 1000 mg of Vitamin C/day during the training period, while CON group (control, n = 12, mean age 72.4 ± 5.5 years and body mass 67.7 ± 7.5 kg) received placebo. Results No significant changes in IL-1, IL-6, IL-10 and CRP mRNA were observed within and between groups. However, there was a clear tendency of a decrease in IL-6 (two-way ANOVA, significant between investigated time points) and an increase in IL-10 mRNA noted in the supplemented group. A significant decrease in CCL2 mRNA was observed only in the CON group (from 2^0.2 to 2^0.1, p = 0.01). Conclusions It can be concluded, that 6 weeks of supplementation and exercise was too short to obtain significant changes in gene expression in leukocytes, but supplementation of 1000 mg vitamin C positively affected IL-6 and IL-10 expression - which are key changes in the adaptation to training. However, changes in body mass, IL1 and CCL2 were positive in CON group. It is possible that Vitamin C during 6 weeks of supplementation could have different effects on the expression of individual genes involved in the immune response. Trial registration Retrospectively registered.